Legal Protection for Doctors in the Use of Telepharmacy for Health Services - Adi Sukrisno; Abdul Kolib; Handar Subhandi Baktiar (International Journal of Social Sciences and Humanities, 2026)
Digital transformation in the health sector has encouraged the development of information technology-based health services, including telepharmacy as a component of the digital health service system. Telepharmacy improves access to health services, service efficiency, and the reach of pharmaceutical care in remote areas that face shortages of health workers. However, the implementation of telepharmacy raises legal issues concerning the distribution of responsibility among doctors, pharmacists, health care facilities, and electronic system providers when service errors or patient harm occur. This study analyzes the legal regulation that should apply to doctors in the use of telepharmacy and identifies legal protection mechanisms that can be provided to doctors in the delivery of digital health services. This study uses normative juridical research with statutory, conceptual, and legal theory approaches. The findings show that digital health regulations in Indonesia, particularly Law Number 17 of 2023 on Health and Government Regulation Number 28 of 2024, have not comprehensively regulated telepharmacy and the distribution of legal responsibility among the relevant parties. This normative gap creates legal uncertainty for doctors as attending physicians and opens the risk of disproportionate criminalization of the profession. This study proposes the Tiered and Distributed Causal Liability Model as a legal construction that allocates responsibility based on each party's level of control, authority, and causal contribution. The model provides proportional legal protection for doctors while ensuring the protection of patient rights in the digital health service system.